2020
DOI: 10.1186/s13195-020-00609-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving the resistance and resilience framework for aging and dementia studies

Abstract: Background: The "resistance vs resilience" to Alzheimer's disease (AD) framework (coping vs avoiding) has gained interest in the field in the last year. In this viewpoint, our effort is (i) to provide clarity to the usage of the framework in the context of the ATN (amyloid/tau/neurodegeneration) system as well as in lifespan and cognitive aging studies and (ii) to discuss the challenges of matching these concepts to specific biological mechanisms. Main body: In the context of the ATN system, the main goal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 13 publications
1
37
1
1
Order By: Relevance
“…Evidence for resistance would be supported by low loads or absence of risk factors, while evidence for resilience would be supported by the exposure to such factors in combination with a higher cognitive performance and/or lower rates of decline. 55 , 56 , 57 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for resistance would be supported by low loads or absence of risk factors, while evidence for resilience would be supported by the exposure to such factors in combination with a higher cognitive performance and/or lower rates of decline. 55 , 56 , 57 …”
Section: Discussionmentioning
confidence: 99%
“…Resilience may be further explained by the build-up of cognitive reserve. 15 , 56 This concept relates to having more neural resources available by inheritance or lifetime training, allowing higher levels of brain damage to accumulate before clinical symptoms appear. 15 We found that next to physical health factors, factors of cognitive reserve such as education, frequency of cognitive activity, and premorbid IQ were associated with cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…has been coined to capture the scientific paradigm that refers to the adaptability that helps to explain differential susceptibility of cognitive abilities or day-to-day function to brain aging, pathology, or insult, and has been described in terms of both resilience and resistance [6]. Indeed, a high cognitive reserve was found to be related to a 47% reduced relative risk of mild cognitive impairment or dementia [7].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…Various heuristic constructs (e.g., cognitive/brain reserve, neural compensation, brain maintenance) have been proposed to describe different aspects of the observed individual differences in brain and cognitive aging trajectories. 1 , 2 Here, we adopt and expand upon a previously proposed framework 3 , 4 that conceptualizes 2 distinct phenomena under the umbrella terms resistance and resilience. Resistance is defined as the brain's ability to avoid age-related senescent and pathologic changes, thereby preserving brain integrity and cognition, despite risk factors such as advanced age or genetic predisposition to Alzheimer disease (AD) pathology.…”
mentioning
confidence: 99%
“…Resilience refers to the brain's ability to cope with accumulating senescent and pathologic changes and preserve brain integrity (brain resilience) or cognitive function (cognitive resilience) in the face of significant pathologic burden. 3 , 4 For example, an elderly APOE ε4/ε4 carrier is at increased risk of accumulating AD neuropathology and subsequent cognitive impairment. Remaining relatively free of neuropathology would indicate resistance, while preserving normal cognition despite β-amyloid and tau accumulation indicates (cognitive) resilience.…”
mentioning
confidence: 99%